Hexagonal boron nitride powder and method for producing same
By controlling the manufacturing process of hexagonal boron nitride powder, especially the heating and cooling rates, hexagonal boron nitride powder with high crystallinity and improved resin thermal conductivity was prepared, solving the problems of insufficient crystallinity and thermal conductivity in the prior art, and making it suitable for heat dissipation materials for electronic components.
Patent Information
- Application Number
- CN202480026026.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-26
- Filing Date
- 2024-02-27
- Publication Date
- 2025-11-18
AI Technical Summary
In the existing technology, although high-purity hexagonal boron nitride single crystals have good crystallinity, there is no research on hexagonal boron nitride powder with high crystallinity that can improve the thermal conductivity of resin.
A method for manufacturing hexagonal boron nitride powder with a ratio of spectral intensity at 227 nm to spectral intensity at 330 nm greater than 1.0, measured by cathodoluminescence, includes processes such as reduction nitriding, acid washing, heating, and cooling, with the heating and cooling rates controlled within a specific range.
A highly crystalline hexagonal boron nitride powder was developed, which significantly improved the thermal conductivity of the resin, making it suitable as a heat dissipation filler.
Smart Images

Figure CN120981422A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a hexagonal boron nitride powder and a method for producing the same. BACKGROUND
[0002] In recent years, with the miniaturization and high power of electronic components, an increase in the amount of heat generated by electronic components has become a problem. Therefore, in order to achieve effective heat dissipation of electronic components, a material having excellent thermal conductivity has been developed.
[0003] By incorporating the hexagonal boron nitride powder in a resin used for electronic components, the thermal conductivity of the resin is improved. Therefore, research and development of the hexagonal boron nitride powder as a thermal conductive filler is actively being conducted. For example, Patent Literature 1 discloses a high-purity hexagonal boron nitride single crystal having an intrinsic ultraviolet light emission band at a wavelength of 235 nm or less.
[0004] PRIOR ART DOCUMENTS PATENT LITERATURE Patent Literature 1: Japanese Patent Application Laid-Open No. 2005-145788 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION The above high-purity hexagonal boron nitride single crystal is a single crystal that is not affected by impurities, and a hexagonal boron nitride powder having high crystallinity has not been reported. It is expected that a hexagonal boron nitride powder having high crystallinity and improved thermal conductivity of a resin will be developed.
[0005] An object of one aspect of the present application is to achieve a hexagonal boron nitride powder having high crystallinity and improved thermal conductivity of a resin.
[0006] MEANS FOR SOLVING THE PROBLEMS In order to solve the above problems, one aspect of the present application relates to a hexagonal boron nitride powder, wherein a ratio of a spectral intensity at a wavelength of 227 nm to a spectral intensity at a wavelength of 330 nm measured by a cathodoluminescence (CL) method is 1.0 or more.
[0007] In addition, one aspect of the present application relates to a method for producing a hexagonal boron nitride powder, comprising the following steps: (1) a reduction nitriding step of heating a raw material mixture containing an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound, and a carbon-containing boron compound in a furnace under a nitrogen atmosphere at a temperature of 1500°C or higher and 1850°C or lower at a temperature increasing rate of 10°C / min or less to obtain a hexagonal boron nitride; (2) an acid pickling step of subjecting the hexagonal boron nitride powder containing unreacted raw materials obtained by the reduction nitriding step to acid pickling; (3) a heating step of heating the hexagonal boron nitride powder after the pickling step to a temperature exceeding 1850°C and less than 2050°C at a temperature increase rate of 5°C / min or less; (4) a cooling step of cooling the hexagonal boron nitride powder after the heating step to a temperature of at least 1550°C at a temperature decrease rate of 5°C / min or less; and (5) a recovery step of taking out the hexagonal boron nitride powder cooled to 50°C or less after the cooling step from the furnace.
[0008] Effects of the Invention According to one aspect of the present invention, a hexagonal boron nitride powder having high crystallinity, which improves the thermal conductivity of a resin composition filled with the same, can be achieved. BRIEF DESCRIPTION OF DRAWINGS
[0009] Figure 1 is a graph showing the measurement results of the CL spectrum in one embodiment of the hexagonal boron nitride powder according to the present invention. DETAILED DESCRIPTION
[0010] In the present specification, "A to B" means A or more and B or less, unless otherwise specified.
[0011] 〔Hexagonal boron nitride powder〕 One aspect of the present invention relates to a hexagonal boron nitride powder, the ratio of the spectrum intensity at a wavelength of 227 nm to the spectrum intensity at a wavelength of 330 nm (CL spectrum intensity at 227 nm / CL spectrum intensity at 330 nm) measured by cathodoluminescence method is 1.0 or more.
[0012] The present inventors have repeatedly conducted detailed studies on hexagonal boron nitride powder, and as a result, have successfully obtained new insights. That is, it has been independently found that, in the production of hexagonal boron nitride powder, by employing specific conditions, a hexagonal boron nitride powder having a CL spectrum intensity at 227 nm / CL spectrum intensity at 330 nm of 1.0 or more can be obtained. Furthermore, it has been independently found that this hexagonal boron nitride powder is a hexagonal boron nitride powder having high crystallinity and close to a single crystal. It has also been independently found that this hexagonal boron nitride powder is a hexagonal boron nitride powder that improves the thermal conductivity of a resin, and is suitable as a heat dissipation filler.
[0013] The cathodoluminescence method is a method of detecting light emitted when electron rays are irradiated to a sample. Cathodoluminescence reflects the properties of crystals (crystal defects, impurities, carrier concentration, stress, etc.). The CL spectrum at 227 nm is a spectrum indicating high crystallinity. The CL spectrum at 330 nm is a spectrum caused by carbon impurities. The CL spectrum intensity can be the peak intensity of the CL spectrum.
[0014] As a measuring device in cathodoluminescence, a known measuring device can be used.
[0015] From the viewpoint of higher crystallinity and further improved thermal conductivity of the resin, the CL spectral intensity at 227 nm / CL spectral intensity at 330 nm is preferably 1.1 or higher, more preferably 1.2 or higher, and even more preferably 1.3 or higher.
[0016] The amount of boron dissolved from the above-mentioned hexagonal boron nitride powder after immersion in a 2 mol / L sulfuric acid aqueous solution at 25°C for 120 minutes, converted to B2O3, is preferably below 250 ppm. The amount of dissolved boron is related to the surface oxygen concentration of the hexagonal boron nitride powder. If the amount of dissolved boron is below 250 ppm, the oxygen concentration on the powder surface is low, and the crystallinity of the hexagonal boron nitride powder is improved. For example, the amount of dissolved boron can be measured by inductively coupled plasma (ICP) luminescence analysis. The above-mentioned amount of dissolved boron can also be below 200 ppm, or even below 180 ppm.
[0017] From the viewpoint of further improving the thermal conductivity of the resin and ease of handling, the average particle size of the above-mentioned hexagonal boron nitride powder is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. Furthermore, from the viewpoint of easily and uniformly dispersible in the resin composition, this average particle size is preferably 90 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less. This average particle size is the average particle size (D50) based on volume.
[0018] From the viewpoint of higher crystallinity and further improved thermal conductivity of the resin, the whiteness of the above-mentioned hexagonal boron nitride powder is preferably 90 or higher. Whiteness is measured using a colorimeter.
[0019] [Method for manufacturing hexagonal boron nitride powder] One aspect of the present invention relates to a method for manufacturing hexagonal boron nitride powder (hereinafter sometimes referred to as "this manufacturing method"), comprising: a reduction nitriding step, an acid washing step, a heating step, a cooling step, and a recovery step. Each step will be described below.
[0020] (Reduction nitriding process) In the reduction nitriding process, a mixture of raw materials containing oxygen-containing boron compounds, a carbon source, oxygen-containing calcium compounds, and carbon-containing boron compounds is heated in a furnace under a nitrogen atmosphere to a temperature above 1500°C and below 1850°C at a heating rate of less than 10°C / min. This process yields hexagonal boron nitride containing unreacted raw materials.
[0021] (raw material) As an oxygen-boron-containing compound, a compound containing both boron and oxygen atoms can be used. Examples of oxygen-boron-containing compounds include boric acid, anhydrous boric acid, metaboric acid, perboric acid, hypoboric acid, sodium tetraborate, and sodium perborate. Among these, readily available boric acid or boron oxide can be preferred.
[0022] As carbon sources, in addition to amorphous carbon such as carbon black, activated carbon, and carbon fibers, crystalline carbon such as diamond, graphite, and nano-carbon can also be used, as well as thermally decomposed carbon obtained by thermally decomposing monomers or polymers. Among these, highly reactive amorphous carbon is preferred, and further, from the perspective of industrial quality control, carbon black is particularly preferred. Other examples of carbon black include acetylene black, furnace black, and thermal black.
[0023] Examples of oxygen-containing calcium compounds include calcium carbonate, calcium bicarbonate, calcium hydroxide, calcium oxide, calcium nitrate, calcium sulfate, calcium phosphate, and calcium oxalate. One or more of these compounds can be used in combination. Calcium oxide or calcium carbonate is preferred. By including an oxygen-containing calcium compound in the raw material mixture and heating it at a heating rate of less than 10°C / min during the reduction nitriding process, highly crystalline hexagonal boron nitride powder can be obtained.
[0024] As an oxygen-containing calcium compound, it forms a high-melting-point complex oxide by combining with oxygen-containing boron compounds, thus preventing the volatilization of the boron compounds. Furthermore, it has been confirmed to act as a catalyst in the direct nitriding reaction of boron carbide.
[0025] As the carbon-boron compound, compounds containing carbon and boron (such as boron carbide) can be used. The particle size of the carbon-boron compound is preferably 1 μm to 500 μm, more preferably 10 μm to 400 μm, and even more preferably 20 μm to 300 μm.
[0026] For example, an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound, and a carbon-containing boron compound can be mixed in the following proportions to obtain a mixture. The ratio of the equivalent mass of the oxygen-containing boron compound (B) to the equivalent mass of the carbon source (C) (B / C elemental ratio) is set to 0.75~1.05. For 100 parts by mass of the total equivalent mass of the oxygen-containing boron compound (B₂O₃) and the carbon source (C), the oxygen-containing calcium compound (calculated as CaO) is set to 5~20 parts by mass. For 100 parts by mass of the total equivalent masses of the oxygen-containing boron compound, carbon source, and oxygen-containing calcium compound (B₂O₃, C, CaO), the carbon-containing boron compound is set to 5~45 parts by mass.
[0027] Regarding the form in which the raw material mixture containing each ingredient is supplied to the reduction nitriding reaction, it can be supplied in powder form or in granular form. For example, the raw materials can be mixed using mixers such as vibratory mills, bead mills, ball mills, Henschel mixers, drum mixers, vibratory stirrers, and V-type mixers.
[0028] In the reduction nitriding process, the heating of the raw material mixture is carried out in a furnace under a nitrogen atmosphere. Examples of gases introduced into the furnace include nitrogen and ammonia. A gas containing a mixture of nitrogen or ammonia and non-oxidizing gases such as hydrogen, argon, or helium can also be used. Nitrogen is preferred as the gas introduced into the heating furnace. Furthermore, regarding nitrogen, nitrogen with a controlled dew point temperature is preferred, preferably below -85°C.
[0029] In the reduction nitriding process, the heating of the raw material mixture is carried out by raising the temperature from 1500°C to a temperature below 1850°C (the maximum reduction nitriding temperature) at a heating rate of 10°C / min or less. By heating at this heating rate, the grain growth rate of the hexagonal boron nitride powder can be slowed down, thereby obtaining hexagonal boron nitride powder with high crystallinity. From the viewpoint that a hexagonal boron nitride powder with higher crystallinity can be obtained by slowing down the grain growth rate of the hexagonal boron nitride powder, the heating rate from 1500°C to the maximum reduction nitriding temperature is preferably 7°C / min or less, more preferably 5°C / min or less, and even more preferably 3°C / min or less.
[0030] In the reductive nitriding reaction, the holding time can be appropriately set according to the needs up to the temperature range of 1500°C. After reaching the maximum reductive nitriding temperature, from the viewpoint of promoting the reductive nitriding reaction, the holding time of the maximum reductive nitriding temperature is preferably 1 hour or more, more preferably 2 hours or more. In addition, the holding time of the maximum reductive nitriding temperature is preferably 10 hours or less, more preferably 5 hours or less.
[0031] The reduction nitriding process can be carried out using known reaction apparatuses that can control the reaction atmosphere. For example, atmosphere-controlled high-temperature furnaces that use high-frequency induction heating or heaters for heating treatment can be used. In addition to batch furnaces, continuous heating furnaces such as pusher tunnel furnaces and vertical reactors can also be used.
[0032] The hexagonal boron nitride powder after the reduction nitriding process can be crushed to adjust it to a specified particle size distribution. Slow crushing using a jet mill, ball mill, hammer mill, or mortar and pestle mill is preferred. Furthermore, the crushed powder can be classified using air classifiers or sieving to adjust it to a suitable particle size.
[0033] (Pickling process) In the pickling process, the hexagonal boron nitride powder containing unreacted raw materials obtained through the reduction nitriding process is pickled. The hexagonal boron nitride powder obtained through the above reduction nitriding reaction contains unreacted raw materials such as oxides and metallic impurities. The pickling process removes these unreacted raw materials, resulting in hexagonal boron nitride powder.
[0034] There are no particular limitations on the acid washing method for hexagonal boron nitride powder containing unreacted raw materials, and known methods can be used without restriction. For example, the following method can be used: put the hexagonal boron nitride powder containing unreacted raw materials obtained after the reduction nitriding reaction into a container, add 5 to 10 times the amount of dilute hydrochloric acid (10 to 20% HCl by mass) containing the hexagonal boron nitride powder containing unreacted raw materials, and let them contact for 4 to 8 hours.
[0035] In addition to hydrochloric acid, other acids used in pickling include nitric acid, sulfuric acid, and acetic acid.
[0036] After pickling, the remaining acid can be removed by washing with pure water. One method is to filter the acid used in the pickling process, then disperse the pickled hexagonal boron nitride powder in an equal volume of pure water and filter again.
[0037] After pickling or washing, the moist lumps can be dried. Drying conditions are preferably atmospheric conditions at 50°C to 250°C or under reduced pressure. The drying time is not specifically specified, but drying until the moisture content is infinitely close to 0% is preferred.
[0038] (Heating process) In the heating process, the hexagonal boron nitride powder obtained by the acid washing process is heated to a temperature exceeding 1850°C but less than 2050°C at a heating rate of less than 5°C / min.
[0039] As a heating step, heating can be carried out under a nitrogen atmosphere. The nitrogen source for the reaction system in the heating step can be supplied using the same method as in the reduction nitriding step. Furthermore, the reaction apparatus can be the same as that used in the reduction nitriding step.
[0040] The heating process for hexagonal boron nitride powder involves raising the temperature at a rate of less than 5°C / min to a temperature exceeding 1850°C but less than 2050°C (then firing to the highest temperature). This heating method yields highly crystalline hexagonal boron nitride powder. However, heating to above 2050°C carries the risk of nitrogen defects causing yellowing and resulting in low-crystallinity hexagonal boron nitride powder.
[0041] There is no particular limitation on the starting temperature for adjusting the heating rate in the heating process. For example, room temperature (20℃~25℃) can be used as the starting temperature for adjusting the heating rate.
[0042] From the perspective of improving the efficiency of the heating process, the preferred initial adjustment temperature for the heating rate is at least 1450°C. This initial adjustment temperature of at least 1450°C includes setting the heating rate only after the temperature of the hexagonal boron nitride powder reaches 1450°C.
[0043] From the viewpoint of obtaining hexagonal boron nitride powder with higher crystallinity, the heating rate in the heating process is preferably 4°C / min or less, more preferably 3°C / min or less.
[0044] After reaching the maximum re-firing temperature, from the viewpoint of ensuring sufficient heating (re-firing) of the hexagonal boron nitride powder, the holding time at the maximum re-firing temperature is preferably 1 hour or more, more preferably 3 hours or more. Furthermore, the holding time at the maximum re-firing temperature is preferably 15 hours or less, more preferably 10 hours or less.
[0045] (Cooling process) In the cooling process, the hexagonal boron nitride powder after the heating process is cooled to at least 1550°C at a cooling rate of 5°C / min or less. Through this cooling process, hexagonal boron nitride powder with a CL spectral intensity at 227 nm / CL spectral intensity at 330 nm of 1.0 or higher can be obtained.
[0046] The temperature of at least 1550°C includes cooling the hexagonal boron nitride powder to 1550°C.
[0047] From the viewpoint that a hexagonal boron nitride powder with a higher CL spectral intensity at 227 nm and a higher CL spectral intensity at 330 nm can be obtained, the heating rate in the cooling process is preferably 4 °C / min or less, and more preferably 3 °C / min or less.
[0048] (Recycling process) In the recycling process, hexagonal boron nitride powder cooled to below 50°C after the aforementioned cooling process is removed from the furnace. By cooling the hexagonal boron nitride powder recovered from the furnace to below 50°C, reactions with moisture in the air can be suppressed. By suppressing this reaction, the increase in the surface oxygen concentration (B2O3 concentration) of the hexagonal boron nitride powder can be prevented, thereby improving the crystallinity of the hexagonal boron nitride powder. Furthermore, by cooling the hexagonal boron nitride powder recovered from the furnace to below 50°C, hexagonal boron nitride powder with a CL spectral intensity at 227 nm / CL spectral intensity at 330 nm of 1.0 or higher can be obtained.
[0049] From the viewpoint of effectively suppressing the reaction with moisture in the air and improving the crystallinity of hexagonal boron nitride powder, the temperature at which the hexagonal boron nitride powder is recovered from the furnace is preferably below 40°C, and more preferably below 30°C.
[0050] [Applications of Hexagonal Boron Nitride Powder] (Resin composition) One aspect of the present invention relates to a resin composition containing the aforementioned hexagonal boron nitride powder. This resin composition, by containing the aforementioned hexagonal boron nitride powder, exhibits high thermal conductivity and is suitable for heat dissipation applications.
[0051] The above-described resin composition can be used for a variety of applications. By mixing with the resins described below to form a thermally conductive resin composition or a thermally conductive molded article, it can be preferably used for, for example, thermal interface materials such as polymer-based heat sinks and phase change plates; organic heat sinks such as thermal tapes, thermal pastes, thermal adhesives, and gap fillers; thermal coatings such as thermal paints and thermal coating layers; thermally conductive resin substrates such as PWB-based resin substrates and CCL-based resin substrates; insulating layers for metal-based substrates such as aluminum-based substrates and copper-based substrates; and sealing materials for power devices; and other applications.
[0052] Examples of resins contained in the above-mentioned resin compositions include: thermoplastic resins such as polyolefins, vinyl chloride resins, methyl methacrylate resins, nylon and fluoropolymers; thermosetting resins such as epoxy resins, phenolic resins, urea resins, melamine resins, unsaturated polyester resins, silicone resins and bismaleimide triazine resins; and synthetic rubbers; etc.
[0053] The above-mentioned resin composition may contain thermally conductive fillers such as aluminum nitride and aluminum oxide, which are known as high thermal conductivity insulating fillers.
[0054] In addition, the above-mentioned resin composition may also contain known polymerization initiators, curing agents, polymerization inhibitors, polymerization retarders, coupling agents, plasticizers, ultraviolet absorbers, pigments, dyes, antibacterial agents, organic fillers, and organic-inorganic composite fillers as compounding agents as needed. Furthermore, without impairing the effects of the present invention, the resin composition may also contain other inorganic fillers.
[0055] From the viewpoint of obtaining higher thermal conductivity, the content of the above-mentioned hexagonal boron nitride powder in the above resin composition is preferably 20 to 80% by volume, more preferably 30 to 70% by volume.
[0056] Regarding the content of the above-mentioned resin in the above-mentioned resin composition, it is equivalent to the value obtained by subtracting the content of hexagonal boron nitride powder from the total volume of the resin composition when the total volume is set to 100% by volume, and the volume of the curing agent is also included. It is preferably 80 to 20% by volume, and more preferably 70 to 30% by volume.
[0057] (Resin sheet) One aspect of the present invention relates to a resin sheet composed of the aforementioned resin composition. The application of this resin sheet is not particularly limited; for example, it can be used for applications such as circuit board applications and heat dissipation applications for electronic components in multilayer printed circuit boards, etc.
[0058] The manufacturing method of the above-mentioned resin sheet is not particularly limited. For example, when the resin is a curable epoxy resin, the manufacturing method of the resin sheet as described below can be adopted, which includes: a mixing step, in which the curable epoxy resin, the above-mentioned hexagonal boron nitride powder and other components are mixed as needed to obtain a curable composition; a molding step, in which the curable composition is shaped into a desired shape; and a curing step, in which the curable composition is cured.
[0059] (Other uses) The hexagonal boron nitride powder according to the present invention, due to its high crystallinity, can also be used as a raw material for boron nitride processed products such as cubic boron nitride or boron nitride molded products, a nucleating agent for engineering plastics, a phase change material, a solid or liquid thermal interface material, a release agent for molten metal or molten glass forming molds, cosmetics, and a raw material for composite ceramics, etc.
[0060] [Overview] The hexagonal boron nitride powder according to the first aspect of the present invention has a ratio of spectral intensity at a wavelength of 227 nm to spectral intensity at a wavelength of 330 nm of 1.0 or more, as measured by cathodoluminescence.
[0061] According to a first aspect of the present invention, the hexagonal boron nitride powder according to the second aspect of the present invention can be configured such that the amount of boron dissolved after immersion in a 2 mol / L sulfuric acid aqueous solution at 25°C for 120 minutes, converted to B2O3, is less than 250 ppm.
[0062] According to the first or second aspect of the present invention, the hexagonal boron nitride powder according to the third aspect of the present invention may be configured such that the average particle size is 2 μm or more and 150 μm or less.
[0063] A resin composition according to a fourth aspect of the present invention contains hexagonal boron nitride powder as described in any one of the first to third aspects of the present invention.
[0064] A resin sheet according to a fifth aspect of the present invention is composed of the resin composition described in the fourth aspect of the present invention.
[0065] A method for manufacturing hexagonal boron nitride powder according to the sixth aspect of the present invention includes the following steps: (1) a reduction nitriding step, wherein a mixture of raw materials containing an oxygen-containing boron compound, a carbon source, an oxygen-containing calcium compound, and a carbon-containing boron compound is heated in a furnace under a nitrogen atmosphere to a temperature of 1500°C or higher and 1850°C or lower at a heating rate of 10°C / min or less, thereby obtaining hexagonal boron nitride; (2) an acid washing step, wherein the hexagonal boron nitride powder containing unreacted raw materials obtained by the reduction nitriding step is subjected to acid washing. (3) A heating process, in which the hexagonal boron nitride powder after the pickling process is heated to a temperature exceeding 1850°C but less than 2050°C at a heating rate of less than 5°C / min; (4) A cooling process, in which the hexagonal boron nitride powder after the heating process is cooled to a temperature of at least 1550°C at a cooling rate of less than 5°C / min; and (5) A recycling process, in which the hexagonal boron nitride powder cooled to below 50°C after the cooling process is removed from the furnace.
[0066] According to a sixth aspect of the present invention, the method for manufacturing hexagonal boron nitride powder according to a seventh aspect of the present invention may be configured such that, in the heating process, the heating rate is adjusted starting from a temperature of at least 1450°C.
[0067] The following embodiments will be provided to illustrate the implementation of the present invention in more detail. Of course, the present invention is not limited to the embodiments described below, and various modifications are possible, which will not be elaborated upon further. Furthermore, the present invention is not limited to the embodiments described above; various modifications can be made within the scope of the claims, and embodiments obtained by appropriately combining the disclosed technical means are also included within the technical scope of the present invention. In addition, all documents described in this specification are incorporated herein by reference.
[0068] Example [Preparation Example 1] Preparation of hexagonal boron nitride powder 259 g of a mixture containing 141 g of boron oxide, 56 g of carbon black, 32 g of calcium oxide, and 30 g of boron carbide was mixed using a ball mill. The mixture was heated to 1500 °C in a graphite-made Taman furnace under a nitrogen atmosphere and held at 1500 °C for 4 hours. The temperature was then increased at a rate of 2 °C / min to the maximum reduction nitriding temperature of 1850 °C. This temperature was then held at 1850 °C for 2 hours to perform the reduction nitriding treatment (reduction nitriding step).
[0069] The reduced-nitrided hexagonal boron nitride powder was placed in a container, and five times the volume of hydrochloric acid (7% HCl) was added. The mixture was stirred at 700 rpm for 24 hours for acid washing. After acid washing, the acid was filtered, and the resulting hexagonal boron nitride powder was dispersed in an equal volume of pure water, followed by filtration. This process was repeated five times, and the powder was then vacuum dried at 200°C for six hours.
[0070] The dried hexagonal boron nitride powder was heated to 1500°C in a graphite-made Taman furnace under a nitrogen atmosphere, and then heated to the maximum re-firing temperature of 1950°C at a rate of 2°C / min. The re-firing process (heating step) was then performed by holding the temperature at 1950°C for 6 hours.
[0071] Next, nitrogen gas is introduced into the furnace to cool it down to 1500°C at a rate of 1°C / minute (cooling process). Then, nitrogen gas is introduced again to cool the furnace down to 25°C, and hexagonal boron nitride powder is recovered from the furnace (recovery process).
[0072] [Example 2] Preparation of hexagonal boron nitride powder Except for changing the cooling rate in the cooling process to 2°C / minute, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0073] [Example 3] Preparation of hexagonal boron nitride powder Except that the maximum re-firing temperature in the heating process was set to 2010°C, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0074] [Example 4] Preparation of hexagonal boron nitride powder Except for changing the cooling rate in the cooling process to 3°C / minute, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0075] [Example 5] Preparation of hexagonal boron nitride powder Except for setting the maximum re-firing temperature in the heating process to 1900°C, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0076] [Comparative Example 1] Preparation of hexagonal boron nitride powder Except for setting the maximum re-firing temperature in the heating process to 2050°C, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0077] [Comparative Example 2] Preparation of hexagonal boron nitride powder Hexagonal boron nitride powder was prepared solely through the reduction nitriding and acid washing processes described in Example 1. Furthermore, in the reduction nitriding process, the temperature was increased from 1500°C to 1850°C at a rate of 1°C / minute. Otherwise, the process was carried out under the same conditions as the reduction nitriding and acid washing processes in Example 1.
[0078] [Comparative Example 3] Preparation of hexagonal boron nitride powder Except for changing the cooling rate in the cooling process to 10°C / minute, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0079] [Comparative Example 4] Except for setting the maximum firing temperature in the heating process to 1800°C, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0080] [Comparative Example 5] Except for increasing the temperature from 1500°C to 1850°C at a rate of 15°C / min during the reduction nitriding process, hexagonal boron nitride powder was prepared following the same steps as in Example 1.
[0081] [Comparative Example 6] Except for cooling the furnace to 100°C in the recycling process before recovering the hexagonal boron nitride powder from the furnace, the hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0082] [Comparative Example 7] Except for the reduction nitriding process performed by the melamine method of thermally decomposing melamine borate at 1950°C, hexagonal boron nitride powder was prepared according to the same steps as in Example 1.
[0083] [Evaluation Example 1] Evaluation of hexagonal boron nitride powder The hexagonal boron nitride powders obtained in Examples 1-5 and Comparative Examples 1-7 were evaluated using the evaluation methods described below.
[0084] (Measured by cathodoluminescence (CL) method) The measurements performed using the CL method were conducted using a Hitachi Schottky field emission SEM S-4300SE and a beam splitter HR-320 (manufactured by Horiba Manufacturing Co., Ltd.) under the following conditions.
[0085] • Electron beam accelerating voltage: 5kV • Sample temperature: 296K • Measurement area: 50×50 μm 2 (Change the location, measure at 3 points) (Measurement of total oxygen content) The total oxygen content in the hexagonal boron nitride powder was measured using an EMGA-620W ceramic oxygen and nitrogen analyzer manufactured by Horiba Corporation.
[0086] (Measurement of total carbon content) The total carbon content in hexagonal boron nitride powder was determined using the EMIA-110 ceramic carbon analysis apparatus manufactured by Horiba Manufacturing Co., Ltd. The powder was burned in an oxygen stream, and the total carbon content was quantified based on the amount of CO and CO2 gases produced.
[0087] (Measurement of B2O3 concentration) 50 g of 2% sulfuric acid aqueous solution and 2 g of hexagonal boron nitride powder were added to a 50 mL Iboy flask. The liquid temperature was adjusted to 25°C while stirring for 1 minute. After standing for 120 minutes, the boron content in the liquid was analyzed using an ICP-based spectrophotometer (iCAP6500, Thermo Fisher Scientific). The measured result was divided by the mass of the hexagonal boron nitride powder used in the experiment to determine the amount of boron dissolved per unit mass of the hexagonal boron nitride powder (B₂O₃ concentration, ppm).
[0088] (Measurement of whiteness) The whiteness of the hexagonal boron nitride powder was measured using a colorimeter ZE7700 (manufactured by Nippon Denshoku Kogyo Co., Ltd.).
[0089] (Average particle size) The average particle size (volume-based average particle size (D50)) of the hexagonal boron nitride powder was measured using a laser diffraction / scattering particle size measuring device MT3000 (manufactured by MicrotracBEL) and by laser diffraction.
[0090] [Evaluation Example 1] Evaluation of the thermal conductivity of the resin composition The hexagonal boron nitride powder obtained in each example and comparative example was filled into epoxy resin to prepare a resin composition, and the thermal conductivity was evaluated. A mixture of 100 parts by weight of epoxy resin (JER828 manufactured by Mitsubishi Chemical Corporation), 5 parts by weight of curing agent (imidazol-based curing agent, curezol 2E4MZ manufactured by Shikoku Kasei Corporation), and 210 parts by weight of methyl ethyl ketone (MEK) as a solvent was prepared. Next, the varnish-like mixture and the hexagonal boron nitride powder were mixed using a rotation / revolution mixer (MAZERUSTAR manufactured by Kurashiki Boshoku Co., Ltd.) to obtain a resin composition where the base resin was 35% by volume and the specific boron nitride powder was 65% by volume, or the base resin was 40% by volume and the specific boron nitride powder was 63% by volume, or the base resin was 45% by volume and the specific boron nitride powder was 55% by volume.
[0091] Regarding the above resin composition, a TESTER Sangyo Co., Ltd. PI-1210 automatic coating machine was used to coat it onto a PET film with a thickness of approximately 180 μm to 220 μm and then dried. The film was then cured under reduced pressure, at a temperature of 200°C, a pressure of 5 MPa, and a holding time of 30 minutes to produce a sheet with a thickness of 150 μm. The sheet was analyzed using a temperature wave thermal analysis device to calculate its thermal conductivity.
[0092] The manufacturing conditions of the hexagonal boron nitride powder in each embodiment and comparative example, as well as the evaluation results of Evaluation Example 1, are shown in Table 1.
[0093] The measured CL spectrum is as follows Figure 1 As shown. Figure 1 In the table, "1" represents the measurement result of the hexagonal boron nitride powder of Comparative Example 2. "2" represents the measurement result of the hexagonal boron nitride powder of Example 4. "3" represents the measurement result of the hexagonal boron nitride powder of Example 2. "4" represents the measurement result of the hexagonal boron nitride powder of Example 1. "5" represents the measurement result of the hexagonal boron nitride powder of Comparative Example 1.
[0094] Table 1
[0095] In Table 1, "Reduction Nitriding Heating Rate" indicates the heating rate from 1500℃ to the maximum re-firing temperature during the reduction nitriding process. "Cooling Rate" indicates the cooling rate from the maximum re-firing temperature back to 1500℃ during the cooling process. "Removal Temperature" indicates the furnace temperature at which the re-fired hexagonal boron nitride powder is recovered from the furnace. "227 nm / 330 nm" represents the ratio of (CL peak intensity at wavelength 227 nm) to (CL peak intensity at wavelength 330 nm).
[0096] As shown in Table 1, it can be seen that the resin composition containing the hexagonal boron nitride powder of the embodiment, which has a CL peak intensity ratio of 227 nm / 330 nm of 1.0 or higher, has a thermal conductivity of more than 15 W / m·K. The hexagonal boron nitride powder of the embodiment is suitable as a heat dissipation filler.
[0097] In Comparative Example 1, where the maximum re-firing temperature was 2050°C, the CL peak intensity ratio of 227 nm to 330 nm was as low as 0.2, and the powder turned yellow. Nitrogen defects and other defects were generated in the yellowed powder, resulting in poor crystallinity. In addition, the resin composition containing hexagonal boron nitride powder of Comparative Example 4, which had a maximum re-firing temperature of 1850°C, had a thermal conductivity of less than 15 W / m·K, and it can be considered that the purification effect brought about by re-firing was not achieved.
[0098] Comparative Examples 3 and 5, which had high heating rates in the heating process (re-firing) or high cooling rates in the cooling process, had a CL peak intensity ratio of 227 nm / 330 nm of 0.9, and a thermal conductivity of the resin composition of less than 15 W / m·K. These results indicate that the heating and cooling rates during re-firing affect the CL peak intensity ratio of 227 nm / 330 nm and the thermal conductivity of the resin composition.
[0099] It was found that the hexagonal boron nitride powder with a high extraction temperature reacted with moisture in the air, resulting in an increase in surface oxygen concentration. This led to a decrease in the crystallinity of the hexagonal boron nitride powder surface and a lower CL peak intensity ratio of 227 nm / 330 nm.
[0100] Industrial availability The hexagonal boron nitride powder of the present invention has high crystallinity and improves the thermal conductivity of the resin, and can be used as a raw material for electronic components.
Claims
1. A hexagonal boron nitride powder, wherein the ratio of the spectral intensity at a wavelength of 227 nm to the spectral intensity at a wavelength of 330 nm, as measured by cathodoluminescence, is greater than 1.
0.
2. The hexagonal boron nitride powder according to claim 1, wherein, The amount of boron dissolved after immersion in a 2 mol / L sulfuric acid aqueous solution at 25°C for 120 minutes, converted to B2O3, is less than 250 ppm.
3. The hexagonal boron nitride powder according to claim 1, wherein, The average particle size is above 2 μm and below 150 μm.
4. A resin composition comprising hexagonal boron nitride powder according to any one of claims 1 to 3.
5. A resin sheet comprising the resin composition of claim 4.
6. A method for manufacturing hexagonal boron nitride powder, comprising the following steps: (1) Reduction nitriding process: In this process, a mixture of raw materials containing oxygen-boron compounds, carbon source, oxygen-calcium compounds and carbon-boron compounds is heated in a furnace under nitrogen atmosphere at a heating rate of less than 10°C / min to a temperature of more than 1500°C and less than 1850°C, thereby obtaining hexagonal boron nitride. (2) Pickling process, which pickles the hexagonal boron nitride powder containing unreacted raw materials obtained by the reduction nitriding process; (3) Heating process, in which the hexagonal boron nitride powder after the pickling process is heated to a temperature of more than 1850°C but less than 2050°C at a heating rate of less than 5°C / min; (4) A cooling process, wherein the hexagonal boron nitride powder after the heating process is cooled to a temperature of at least 1550°C at a cooling rate of less than 5°C / min; and (5) Recovery process, in which the hexagonal boron nitride powder cooled to below 50°C after the cooling process is removed from the furnace.
7. The method for manufacturing hexagonal boron nitride powder according to claim 6, wherein, In the heating process, the heating rate is adjusted starting from a temperature of at least 1450°C.
Citation Information
Patent Citations
High-luminance ultraviolet ray-emitting hexagonal boron nitride single crystal, its producing method, and high-luminance ultraviolet ray-emitting element
JP2005145788A
